2019
DOI: 10.1055/s-0039-3401804
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Patient Motivations and Impact of Asian Blepharoplasty

Abstract: To date, patient motivations for Asian blepharoplasty and the surgery's impact on quality of life have not been quantified. Here, we employed structured interviews and a web-based survey to better characterize patient motivations for Asian blepharoplasty and the impact of Asian blepharoplasty on self-reported domains of happiness, self-esteem, attractiveness, social life, and professional life. Structured interviews were conducted to inform a web-based survey regarding Asian blepharoplasty. Survey respondents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…4 Prior studies have addressed patient satisfaction following blepharoplasty, but there is a dearth of literature specifically analyzing the primary pre-and postoperative queries and concerns of patients. [5][6][7][8] As with many elective cosmetic procedures, patients present with a list of questions that frequently influence their decision to pursue surgical intervention. In fact, an analysis of plastic surgery satisfaction by Chen et al found that one of the highest correlated factors for a patient to recommend a practice or provider to someone else was the provider's ability to address patient questions.…”
Section: Introductionmentioning
confidence: 99%
“…4 Prior studies have addressed patient satisfaction following blepharoplasty, but there is a dearth of literature specifically analyzing the primary pre-and postoperative queries and concerns of patients. [5][6][7][8] As with many elective cosmetic procedures, patients present with a list of questions that frequently influence their decision to pursue surgical intervention. In fact, an analysis of plastic surgery satisfaction by Chen et al found that one of the highest correlated factors for a patient to recommend a practice or provider to someone else was the provider's ability to address patient questions.…”
Section: Introductionmentioning
confidence: 99%